Variations of Surveillance Practice for Patients with Bone Sarcoma: A Survey of Australian Sarcoma Clinicians. (28th February 2017) - Lewin, Jeremy; Thompson, Kate; Bae, Susie; Desai, Jayesh; Strong, Robyn; Caruso, Denise; Howell, Deborah; Herschtal, Alan; Sullivan, Michael; Orme, Lisa
Abstract : Introduction . After treatment, bone sarcoma patients carry a high chance of relapse and late effects from multimodal therapy. We hypothesize that significant variation in surveillance practice exists between pediatric medical oncology (PO) and nonpediatric medical oncology (NP) sarcoma disciplines. Methods . Australian sarcoma clinicians were approached to do a web based survey that assessed radiologic surveillance (RS) strategies, late toxicity assessment, and posttreatment psychosocial interventions . Results . In total, 51 clinicians responded. No differences were identified in local disease RS. In metastatic disease response assessment, 100% of POs (23/23) and 93% of NPs (24/26) conducted CT chest. However, this was more likely to occur for NPs in the context of a CT chest/abdomen/pelvis (NP: 10/26; PO: 1/23; p = 0.006 ). POs were more likely to use CXR for RS (p = 0.006 ). POs showed more prescriptive intensity in assessment of heart function (p = 0.001 ), hearing (p < 0.001 ), and fertility (p = 0.02 ). POs were more likely to deliver written information for health maintenance/treatment summary (p = 0.04 ). The majority of respondents described enquiring about psychosocial aspects of health (n = 33 /37, 89%), but a routine formal psychosocial screen was only used by 23% (n = 6 /26). Conclusion . There is high variability in bone sarcoma surveillance between PO and NP clinicians. Efforts to harmonize approaches would allow early and late effects recognition/intervention and facilitate improved patient care/transition and research.